TAʿLĪM KITĀB AMṮILATI FĪ MAʿHAD AL-FALĀH WA MAʿHAD SIRĀJUL HUDĀ KALĪMANTĀN AL-JANŪBIYYAH - Muhammad Azhari (UIN ANTASARI, 2020)
AbstractThis study aims to (1) find out how the Amtsilati learning process at the Al Falah Islamic Boarding School and Sirajul Huda Islamic Boarding School (2) Know how the planning and strategies are in teaching it and how the students feel after learning Amtsilati. This research belongs to the type of qualitative research, which takes place at the Al Falah Islamic Boarding School and the Sirajul Huda Islamic Boarding School. Therefore, the data collection technique was obtained from informants, events and documents. The collected data is then analyzed by interactive model analysis which includes data reduction, data presentation, conclusion drawing and verification. The results of this study indicate that, the basic concepts used by the Amtsilati method are as follows: A systematic discussion of the Amtsilati material begins with simple examples and is also presented in a simple manner. The characteristics of Amtsilati learning are reading and memorizing. The approach used in teaching Amtsilati is to repeat (memorize) and instruct (expand) the material. The evaluation of Amtsilati learning is an oral and written test. The purpose of the Amtsilati method is for students to be able to read the yellow book, within six months.